Eight keys - LaFleur, Suzanne M. (New York : Wendy Lamb Books, 2011)
When twelve-year-old Elise, orphaned since age three, becomes disheartened by middle school, with its bullies, changing relationships, and higher expectations, keys to long-locked rooms and messages from her late father help hercope.
Booklist
Pub Weekly
School Library Journal
Booklist, September 2011
Pub Weekly, June 2011
School Library Journal, August 2011
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Orphans -- Juvenile fiction; Schools -- Juvenile fiction; Self-actualization (Psychology) -- Juvenile fiction; Families -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Orphans -- Fiction; Schools -- Fiction; Self-actualization (Psychology) -- Fiction; Family life -- Fiction; Friendship -- Fiction; Middle schools -- Fiction; Orphans -- Fiction; School stories; Self-realization -- Fiction